Respons Sosial Masyarakat terhadap Banjir di Aceh Tamiang : Tinjauan Literatur dalam Perspektif Teori Jurgen Habermas - Maharani Safitri; Rika Maryam; Oktaviana Br Ginting M; Vieronica Varbi Sununianti; Istiqoma Istiqoma; Deni Aries Kurniawan (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
Flood disasters have repeatedly affected Aceh Tamiang Regency for over fifteen years, causing significant material and socio-cultural losses. This study aims to examine the social response of the community through a literature review approach, using Jurgen Habermas's Communicative Action Theory as the analytical framework. Data were collected systematically from national journal articles, scientific proceedings, and academic reports related to flood mitigation and community social response in Aceh Tamiang. Data analysis was conducted using content analysis and thematic analysis techniques. The findings reveal that the community's response is primarily driven by local solidarity rooted in cultural values and local wisdom such as hadih maja. In Habermasian terms, this social response reflects the lifeworld domain, manifesting in voluntary collective action. However, a structural tension exists between the government's top-down system and the community's communicative rationality. Effective disaster mitigation requires the development of participatory public spaces that bridge the system and lifeworld, enabling the transformation from instrumental action to communicative action, thereby strengthening collective resilience against flood disasters.